RNA editing is induced by type I interferon in esophageal squamous cell carcinoma. Issue 7 (July 2017) - Zhang, Jinyao; Chen, Zhaoli; Tang, Zefang; Huang, Jianbing; Hu, Xueda; He, Jie
In recent years, abnormal RNA editing has been shown to play an important role in the development of esophageal squamous cell carcinoma, as such abnormal editing is catalyzed by ADAR (adenosine deaminases acting on RNA). However, the regulatory mechanism of ADAR1 in esophageal squamous cell carcinomas remains largely unknown. In this study, we investigated ADAR1 expression and its association with RNA editing in esophageal squamous cell carcinomas. RNA sequencing applied to esophageal squamous cell carcinoma clinical samples showed that ADAR1 expression was correlated with the expression of STAT1, STAT2, and IRF9 . In vitro experiments showed that the abundance of ADAR1 protein was associated with the induced activation of the JAK/STAT pathway by type I interferon. RNA sequencing results showed that treatment with type I interferon caused an increase in the number and degree of RNA editing in esophageal squamous cell carcinoma cell lines. In conclusion, the activation of the JAK/STAT pathway is a regulatory mechanism of ADAR1 expression and causes abnormal RNA editing profile in esophageal squamous cell carcinoma. This mechanism may serve as a new target for esophageal squamous cell carcinoma therapy.